(untitled) (Research, Society and Development, 2025)
Adolescence is usually characterized as the second decade of life, approximately between the ages of 10 and 19, where the process of evolution occurs in the biopsychosocial, behavioral, physiological and anatomical spheres. However, this stage of life is one in which several factors directly influence the development of this adolescent’s personality. The general objective is to discuss teenage pregnancy, emphasizing the physiological, mental, and social aspects. The research is field- based, descriptive and with a qualitative-quantitative approach, carried out with primary care nurses. The study involved 10 randomly selected primary care nurses who provide prenatal care to pregnant adolescents. Data collection was conducted between February and May 2025 through a questionnaire administered to nurses who worked with pregnant adolescents during prenatal care in primary care. This instrument gathered information regarding the participants’ socioeconomic profile, as well as specific questions about prenatal care. Humanized care for pregnant adolescents should be nonjudgmental, prioritizing listening, emotional support, and the creation of bonds of trust. It’s essential to establish a safe environment that promotes autonomy and commitment to prenatal care. Techniques such as discussion groups and family involvement reinforce care and combat stigma. Teenage pregnancy is a complex and multifaceted reality that requires a sensitive and receptive approach from healthcare professionals, especially nurses. This study sought to highlight the importance of a humanized approach from nurses regarding this experience, considering the adolescent as a developing individual who requires comprehensive attention, respect, and emotional support.